A Bibliometric Analysis of Tax Evasion Issues in the Last Decade - Bani Alkausar; Prinintha Nanda Soemarsono; Nitami Galih Pangesti (TIJAB (The International Journal of Applied Business), 2021)
This examination to discover the pattern of research publications on tax evasion issues. This article aims to unveil and to map research trends in tax evasion issues. By using bibliometric approach, all research publications related to tax evasion issues in the online Scopus database were analyzed. The authorship, number of citations, journal sources, institutions, and countries, were examined. The result showed that the number publications in this area are still dominated by western countries (USA is the most influential country in research publication related to tax evasion issues). It is believed that research funding factors became one of the factors why the Western countries still dominate the number of publications nowadays. The results of this study also conclude that the issue of tax evasion are becoming more popular among academics within the area of the taxation. In addition, this study reveals that the development of research publications in this area is growing.